LUNTURNYA SEKTOR PERTANIAN DI PERKOTAAN - Gultom, Ferdi; Harianto, Sugeng (UNIVERSITAS SEBELAS MARET (UNS), 2022)
The agricultural sector is an important sector for food security in Indonesia. However, the government only focused on development through the industrial sector, that agriculture faded away due to the entry of the modern sector through the central state-satellite relationship. This can be seen in the increasingly widespread conversion of agricultural land in urban areas. This study aims to describe how the decline of the agricultural sector in urban areas. This research uses a literature study approach. Data is obtained from news sources, to journals that explain the development of the industrial sector that shifts agricultural land. The data were analyzed using the Miles and Huberman model. The data are classified according to the problem formulation, then reduced to an understandable conclusion. This study uses dependency theory to help analyze the data. Dependency theory was chosen because it can explain the underdevelopment of satellite countries due to the modern sector. The results of this study indicate that the agricultural sector in urban areas is fading, due to the decrease in agricultural land, due to the widespread conversion of land for industry, infrastructure, and settlements. The regeneration of farmers has decreased, due to the lack of interest in becoming a farmer.Keywords: Agricultural Sector, Urban, Addiction, FadeÂ AbstrakSektor pertanian merupakan sektor penting untuk ketahanan pangan di Indonesia. Namun demikian, pemerintah hanya berfokus pada pembangunan melalui sektor industri, sehingga pertanian luntur akibat masuknya sektor modern melalui hubungan negara pusat-satelit. Hal tersebut terlihat alih fungsi lahan pertanian yang sering terjadi di perkotaan. Penelitian ini bertujuan menggambarkan bagaimana lunturnya sektor pertanian di perkotaan. Penelitian ini menggunakan pendekatan studi kepustakaan. Data didapatkan melalui sumber berita, hingga jurnal yang menjelaskan pembangunan sektor industri yang menggeser lahan pertanian. Analisis data menggunakan menggunakan Model Miles dan Huberman. Data diklasifikasikan sesuai dengan rumusan masalah, kemudian direduksi menjadi kesimpulan yang dapat dipahami. Penelitian ini menggunakan teori ketergantungan untuk membantu menganalisis data. Teori ketergantungan dipilih sebab dapat menjelaskan keterbelakangan negara satelit dikarenakan sektor modern. Hasil penelitian ini menunjukan bahwa sektor pertanian di perkotaan semakin luntur, karena lahan pertanian yang semakin berkurang, karena maraknya alih fungsi lahan untuk industri, infrasturkur, dan pemukiman. Regenerasi petani menurun, akibat tidak ada minat menjadi petani.Kata Kunci: Sektor Pertanian, Perkotaan, Ketergantungan, Luntur